2022
DOI: 10.4103/ijo.ijo_3007_21
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of lens parameters in patients with various subtypes of primary angle-closure disease and the normal population: A prospective study

Abstract: Purpose: To assess the role of lens parameters in the detection and progression of primary angle-closure disease (PACD) by combining A-scan and A-scan optical coherence tomography (AS-OCT) parameters. Methods: A cross-sectional study was conducted in a tertiary health-care center in eastern India. A total of 91 study subjects including cases and controls were included in the study. The parameters studied were lens thickness (LT), lens axial factor (LAF)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…[20] In a study by Chakrabarti et al, different lens parameters were analyzed, and the mean lens thickness was more in all subtypes of angle closure disease (4.24 ± 0.84 to 5.02 ± 0.18 mm) compared to the control group (4.04 ± 0.46 mm) and was statistically signi cant (P < 0.01). [21] These ndings were similar to that of our study. It was also observed that there was a direct correlation between increasing age and lens thickness, which again correlated directly with a shallowing of the anterior chamber.…”
Section: Discussionsupporting
confidence: 92%
“…[20] In a study by Chakrabarti et al, different lens parameters were analyzed, and the mean lens thickness was more in all subtypes of angle closure disease (4.24 ± 0.84 to 5.02 ± 0.18 mm) compared to the control group (4.04 ± 0.46 mm) and was statistically signi cant (P < 0.01). [21] These ndings were similar to that of our study. It was also observed that there was a direct correlation between increasing age and lens thickness, which again correlated directly with a shallowing of the anterior chamber.…”
Section: Discussionsupporting
confidence: 92%
“…AS-OCT also has the advantage of a longer scan depth, which allows the visualization of the lens. Thicker lenses with greater lens vaults were found to be important anatomical features in angle-closure eyes by AS-OCT, revealing the crucial role of the lens in the pathogenesis of angle-closure disease [38][39] . Other factors associated with narrow ACA found by UBM and AS-OCT include increased iris thickness, greater iris curvature, larger iris area, and iris volume [40][41][42] .…”
Section: Discussionmentioning
confidence: 96%